2015
DOI: 10.5901/mjss.2015.v6n1s1p517
|View full text |Cite
|
Sign up to set email alerts
|

Should PLCs Diversify into Related or Unrelated Industries? Evidence from Malaysia

Abstract: The primary issue in diversification strategy is concerning its type. A large body of research on the relative effect of related versus unrelated diversification still remains inconclusive. Scholars have been studying this topic through different research designs and in different contexts, although a greater part of the research was conducted in western economies. Importantly, certain scholars have asserted that powerful conclusions could be produced if product diversification is measured using powerful techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…Organizational performance represents an organization’s effectiveness. Performance is normally defined in terms of financial and non-financial components which are related to the extent to which an organization achieves its goals and objectives (Mehmood & Hilman, 2015; Sriviboon & Jermsittiparsert, 2019). To exemplify, an organization’s productivity, market growth and sales growth are its financial components.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Organizational performance represents an organization’s effectiveness. Performance is normally defined in terms of financial and non-financial components which are related to the extent to which an organization achieves its goals and objectives (Mehmood & Hilman, 2015; Sriviboon & Jermsittiparsert, 2019). To exemplify, an organization’s productivity, market growth and sales growth are its financial components.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research papers have highlighted that synchronization in strategic planning is bene¯cial for companies with related businesses rather than those with unrelated businesses [David (2011); Gupta et al (2007); Mehmood and Hilman (2015)]. Synchronization allows related multi-business¯rms to achieve competitive Fig.…”
Section: Targeting¯rms: Related Multi-business Unit¯rmsmentioning
confidence: 99%
“…Moreover, having taken into consideration that related multi-business companies can bene¯t from synchronization in strategic planning more than unrelated multibusiness companies [David (2011); Gupta et al (2007); Mehmood and Hilman (2015)], this research focuses on related multi-business companies with multiple business units.…”
Section: Literature Gapmentioning
confidence: 99%
“…Besides, the incentives given by the Malaysia's government has surged Malaysian firms to engage in the diversification strategies. Mehmood and Hilman (2015) reported that there were more than 70 percent of public listed firms on the main market of Bursa Malaysia from 2010 to 2012 engaging in diversification strategies. In term of corporate strategic financial policy, firm's diversification strategies are predicted to affect the decision in firm's capital structure (Hamyat, Sarita, Hasbudin, & Sujono, 2017).…”
Section: Introductionmentioning
confidence: 99%